Compensation Effect on Performance Employees at PT. People's Bank Indonesia Tbk. Office Polewali Branch - Aswar Rahmat (ProBisnis : Jurnal Manajemen, 2022)
The purpose of this study was to examine the effect of compensation on employee performance at PT. Bank Rakyat Indonesia Tbk. Polewali Branch Office. The type of data used is quantitative data and the data source in this study is primary data. This research is a research with a quantitative approach. Research data obtained from questionnaires and interviews directly by employees of PT. Bank Rakyat Indonesia Tbk. Polewali Branch Office. The sampling technique used is Simple Random Sampling with 30 respondents. The data analysis technique used is simple linear regression analysis. The results of this study indicate that compensation, in this case safety guarantees, has a positive effect on employee performance, especially enthusiasm for work and compliance with company SOPs at PT. Bank Rakyat Indonesia Tbk. Polewali Branch Office, proven by the t count, which is 11.415 > from the t table value, which is 1.703 and the significance level is smaller than the alpha value , which is 0.000 <0.05. The coefficient of determination (R 2 ) is 0.823 which indicates that the change in the dependent variable is 82.3% while the remaining 17.7% is explained by other factors outside the regression model that has been analyzed.